Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Nasabah Di PT Bank Danamon Indonesia Cabang Bintaro Tangerang Selatan - Endah Dwi Rossanti (Journal of Economics and Business UBS, 2019)
This study aims to examine and analyze the effect of service quality and product quality on customer satisfaction in PT Bank Danamon Bintaro Branch South Tangerang. Data was collected through questionnaires distributed and implemented on 100 (one hundred) customers at PT Bank Danamon Bintaro Branch. Data analysis in this study using SPSS version 20. Penenlitian is done sampling by non probability sampling and using accidental sampling method. While the data testing techniques used in this study include the validity test with factor analysis, reliability test with Alpha Cronbach. Test the classical assumption and multiple linear regression analysis, to test and prove the research hypothesis. The results of the analysis show that service quality has an effect on customer satisfaction and product quality also has an effect on customer satisfaction. Based on the results of tests conducted with partial test (t test) there is a positive correlation of service quality variable to customer satisfaction. Similarly, simultaneous test (F test) shows that overall variable of service quality influence (X1) and product quality (X2) have significant influence to customer satisfaction. R Square value of 0.664, means that the quality of service and product quality are together able to explain customer satisfaction variable of 66.4% while the rest of 33.6% are other factors not examined in this study.